Shinto Funerals in the Edo Period - Kenney, Elizabeth (Japanese journal of religious studies, 2000)
Nowadays very few people in Japan have a Shinto funeral. But things might have turned out differently if Shinto activists during the Edo and Meiji periods had achieved their goal of making the Japanese way of death the "kami way," or making Shinto the Japanese way of death. This article presents a detailed look at the mortuary rites for two Shinto priests, one of whom died in the late sixteenth century and the other in the mid-eighteenth century. The first case is the earliest recorded example of a Shinto funeral. The second case, of no particular historical significance, is a funeral that was in part an attempt to replicate the funerals of Japanese mythology. Neither case can be deemed typical, and each is interesting precisely for its specificity. This article concludes with a look at a short essay by another Shinto priest who loathed Shinto funerals.